2021
DOI: 10.1021/acs.energyfuels.0c03394
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of Tight Sandstone Petrophysical Properties in Unconventional Oil Reservoirs with NMR and Rate-Controlled Porosimetry

Abstract: Characterization of the pore size distribution of tight sandstone is of great significance for the effective development of tight oil resources. This paper analyzed the fractal characteristics of pore spaces of tight sandstones from the Yanchang Formation in the Ordos Basin of China with NMR and rate-controlled porosimetry (RCP). A new NMR fractal analysis method that considers the movable fluid distribution was proposed. Compared with the conventional NMR fractal analysis metrics, the fractal dimensions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…The pores in a tight reservoir can be classified according to the transverse relaxation time (T 2 ), Peng et al (2018) reported that the pores could be divided into micro-pore (T 2 ≤ 30 ms), mesopore (30-90 ms), macropore (90-200 ms) and super macropore (T 2 > 200 ms). According to the fluid movement in the pores, the pores can be classified into completely unmovable pores, partially movable pores, and completely movable pores (Wang et al 2021). Four characteristic points in the NMR T 2 spectrum were selected, and the pores were divided into nanopores, micro-pores, meso-pores and macropores (Dai et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pores in a tight reservoir can be classified according to the transverse relaxation time (T 2 ), Peng et al (2018) reported that the pores could be divided into micro-pore (T 2 ≤ 30 ms), mesopore (30-90 ms), macropore (90-200 ms) and super macropore (T 2 > 200 ms). According to the fluid movement in the pores, the pores can be classified into completely unmovable pores, partially movable pores, and completely movable pores (Wang et al 2021). Four characteristic points in the NMR T 2 spectrum were selected, and the pores were divided into nanopores, micro-pores, meso-pores and macropores (Dai et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The pores in a tight reservoir exhibit self-similarity. Compared with classical European geometry, the fractal dimension can describe the heterogeneity and complexity of pores (Krohn and Thompson 1986;Krohn 1988;Jin et al 2017a, b;Guo et al 2019;Wang et al 2019aWang et al , b, 2020Wang et al , 2021Wu et al 2020Wu et al , 2022Yang et al 2021). Pores with fractal dimensions below 2 and above 3 have a weak influence on the pore structure (Guo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The capillary tube model effectively describes the spontaneous imbibition process and upscales the pore‐scale flow behavior to the core‐scale flow behavior based on the pore size distribution 11,32 . The fractal characteristics of the pore size distribution in tight sandstones have been demonstrated with mercury intrusion porosimetry, nuclear magnetic resonance, 33 and N 2 adsorption 34 . In fact, combined with the capillary tube model, the fractal theory has been widely applied to represent the pore size distribution and investigate the mechanism of spontaneous imbibition 35,36 …”
Section: Introductionmentioning
confidence: 99%